Stability of hydrophobic lipase derivatives immobilized on organic polymer beads - Basri, M.; Ampon, K.; Wan Yunus, W.M.Z.; A. Razak, C.N. (Humana Press, 1994)
Lipase from Candida rugosa was immobilized by attaching various hydrophobic groups to the enzyme molecule and adsorbing these hydrophobic lipase derivatives on several organic polymer beads. The immobilized enzymes were more thermostable in organic solvents compared to the native and modified Upases. Thermostability was highest with ΧAD2 beads, followed by ΧAD7 and RCOOH. Initially modifying the enzyme with hydrophobic modifiers did not have any effect on the enzyme thermostability. The best conditions for storing these enzyme preparations were at very low temperature in the lyophilized form and in a solution containing the reaction substrate. Interestingly, PEG-lipase immobilized on ΧAD7 beads showed increased operational stability when used in a stirred-tank reactor. The operational stability was further increased by a mild glutaraldehyde treatment of the enzyme preparation. © 1994 Humana Press Inc.